1235. Transmission of Genetically Related, Multidrug Resistant, and Invasive Vancomycin-Resistant Enterococci (VRE) Between Patients and Rooms on the Stem Cell Transplant (SCT) and Leukemia (LKM) Units. (26th November 2018) - El Haddad, Lynn; Hanson, Blake; Arias, Cesar; Otero, Glen; Harb, Cynthia; Ghantoji, Shashank S; Stibich, Marc; Chemaly, Roy F
Abstract: Background: VRE are a major cause of morbidity and mortality in immunocompromised patients. Tracking the dissemination of VRE strains is crucial to understand the dynamics of infections, emergence, and spread of VRE in the hospital setting. Methods: Whole-genome sequencing (WGS) and phylogenetic analyses were performed to identify dominant VRE strains and potential transmission networks between patients and their rooms on the leukemia (LKM) and the stem cell transplant (SCT) units, located on two consecutive floors. We included 35 VRE-positive rectal swabs from SCT and LKM patients, and 55 environmental swabs from the patients' main rooms and bathrooms. Sequence types, drug resistance genes, virulence genes, and patients' outcomes were also determined. Results: We identified VRE strains with newly described sequence types (ST) such as ST736, ST494, and ST772 which were isolated from both floors. One VRE genetic lineage belonged to ST494 (only previously isolated in Peru and was the only VanB-type strain). All other strains harbored the vanA gene. We observed highly genetically related strains transmitted between distinct rooms, floors, and time periods within the hospital in a period of 1 month (figure). Of five VRE bacteremia events, three strains were lacking the pili operon fms14-17-13 (ST203) and the remaining two were resistant to daptomycin (ST736, ST664) (figure). Of 10 patients harboring daptomycin-resistant strains, only 3 (30%) were exposed to daptomycin within 18 months before strain recovery. Conclusion: Our findings confirmed horizontal transfer of highly related genetic lineages of multidrug resistant and invasive VRE strains between SCT and LKM patients and their room environment. New STs were identified and some correlated with bacteremia events. The use of a routine real-time WGS can characterize VRE strains and identify potential reservoirs of transmission in the healthcare setting in order to design interventions to prevent and control the spread of opportunistic and highly resistant organisms. Disclosures: C. Arias, Merck & Co., Inc.: Grant Investigator, Research support. MeMed: Grant Investigator, Research support. Allergan: Grant Investigator, Research support. M. Stibich, Xenex Services: Employee, Salary. R. F. Chemaly, Xenex Services: Consultant and Grant Investigator, Research grant.